MicroRNA-20a Suppresses Tumor Proliferation and Metastasis in Hepatocellular Carcinoma by Directly Targeting EZH1 - Zhang, Qianqian; Deng, Xiaohong; Tang, Xiuxin; You, Ying; Mei, Meihua; Liu, Danping; Gui, Lian; Cai, Yan; Xin, Xiaoping; He, Xiaoshun; Huang, Junqi (Frontiers in Oncology, 2021)
Abstract Purpose Hepatocellular carcinoma (HCC), a worldwide leading cause of morbidity and mortality, is the most frequent primary liver tumor. Most HCC patients are diagnosed with advanced liver cancer, resulting in a very low 5-year survival rate. Thus, there is an urgent need for the development of targeted therapies. In this study, we aimed to investigate the effect and mechanism of miR-20a/EZH1 axis on the proliferation and metastasisof HCC, as well as the inhibitory effect of EZH1/2 inhibitor UNC1999 on hepatocellular carcinoma in vitro. Materials and Methods The expression of miR-20a in human hepatocellular carcinoma tissues and hepatocellular carcinoma cell lines was detected by qRT-PCR. The expression of proteins was analyzed by immunohistochemistry and western blot. Luciferase assay was used to verify whether miR-20a targets EZH1 or EZH2. The effect of miR-20a on HCC progression was studied in vivo and in vitro. RNA sequencing (RNA-seq) was performed to screen differentially expressed genes in Huh7 and SMMC7721 cell linesafter UNC1999, sorafenib, and the combination treatments. Results In this study, we showed that there was a lower expression of miR-20a in both HCC tissues and HCC cell lines. MiR-20a inhibited the proliferation and migration of SMMC7721 and Huh7 cells. The results of the luciferase assay and western blot analysis revealed that miR-20a directly targeted EZH1, a histone methyltransferase. We demonstrated that miR-20a negatively regulated EZH1 expression and inhibited the proliferation and metastasis of HCC by reducing H3K27 methylation. The EZH1/2 inhibitor, UNC1999，can inhibit proliferation and metastasis of Huh7 and SMMC7721 cells, and enhance the inhibitory effect of sorafenib on hepatoma cell lines. Conclusion We demonstrated that miR-20a suppresses tumor proliferation and metastasis in hepatocellular carcinoma by directly targeting EZH1. EZH1 inhibitor UNC1999 has inhibitory effects on metastasis, invasion, and migration of HCC.